The Effect of Taxpayer Awareness and Tax Sanctions on Taxpayer Compliance of Personal Persons with Religiosity as Moderation - Hardini Indah Roshita; Umaimah Umaimah (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the effect of taxpayer awareness, tax sanctions and religiosity on taxpayer compliance. The population in this study were all individual taxpayers in the city of Gresik, sampling using random sampling method, and the number of samples as many as 100 respondents. The results of hypothesis testing in this study indicate that taxpayer awareness, tax sanctions and religiosity have a significant effect on taxpayer compliance, while the interaction between religiosity and taxpayer awareness and tax sanctions has no significant effect on taxpayer compliance.